Integrated dentistry: Periodontal treatment, orthodontic and prosthetic. - Maita Véliz, Luis Vidal (2006)
The needs of the dental treatment in the patients foroud a mutidiscipling work. It report a clinical case of one patient who exhibilidad a advanced periodontal disease, whith migration of the anterior upper teeth after the periodontal treatment (Motivation oral periodontal hygienic, root planning, periodontal autologos bore injerto it mode the orthodontic in the anterior upper tooth. Finally the patient recivea a bridge in the upper segment.